Recent Liquid Crystal Photonics Research in HKUST - Chigrinov, Vladimir G.; Kwok, Hoi Sing; Poon, Andrew; Bermak, Amine (Photonics Letters of Poland, 2011)
We have characterized liquid crystal (LC) materials and electrooptical modes, as well as new LC configurations suitable for fiber optical applications. New LC based tunable photonic devices were also proposed. The basic achievements were made using the photoaligning and photopatterning technology. Full text: PDF References: V.G. Chigrinov, V.M. Kozenkov, H.S. Kwok, Photoalignment of Liquid Crystalline Materials: Physics and Applications, (Wiley 2008). Vladimir G. Chigrinov, "Liquid Crystal Photoalignment: A New Challenge for Liquid Crystal Photonics", Photonics Letters of Poland, Vol. 2 (3), 104-106 (2010). [CrossRef] S.R. Nersisyan, N.V. Tabiryan, D.M. Steeves, B.R. Kimball, V.G. Chigrinov, H.S. Kwok, "Study of azo dye surface command photoalignment material for photonics applications", Appl. Opt. 49(10), 1720 (2010). [CrossRef] Li Shuang Yao, Tao Du, Vladimir Chigrinov, Hoi Sing Kwok, and Li Xuan, "A novel composite alignment layer for transflective liquid crystal display", J. Phys. D., Vol.43, 415505 (2010). [CrossRef] A. V. Dubtsov, S. V. Pasechnik, Alexei D. Kiselev, D. V. Shmeliova, and V. G. Chigrinov, "Electrically -assisted lightinduced azimuthal gliding of the nematic liquid-crystal easy axis on photoaligned substrates", Phys. Rev. E, 82, 011702 (1-6), (2010). [CrossRef] A.G. Maksimochkin, S.V. Pasechnik, G.I. Maksimochkin, V.G. Chigrinov, "Electrically controlled waveguide mode in LC layer for fiber optic applications",Opt. Comms., Vol.283, pp. 3136-3141 (2010). [CrossRef] Evgeny Pozhidaev, and Vladimir Chigrinov, SID?10 Conference, 27-2, Seattle, Washington, USA, May, 2010. Evgeny Pozhidaev, Vladimir Chigrinov, Valery Vashenko et al., (submitted to SID’11 Conference), May 2011, USA. Xiaojin Zhao, Amine Bermak, Farid Boussaid, and Vladimir G. Chigrinov, "Liquid-crystal micropolarimeter array for full Stokes polarization imaging in visible spectrum", Optics Express, Vol. 184, No. 17, pp. 17776- 17787 (2010). [CrossRef] S. Valyukh, I. Valyukh, V. Chigrinov, H. S. Kwok, and H. Arwin, "Liquid crystal light deflecting devices based on nonuniform anchoring",Appl. Phys. Lett., 97, 231120-1- 231120-3, (2010). [CrossRef] F. Fan, M.-C. Tseng, A. Murauski, H.S. Kwok, V. Chigrinov, LCTp4-12, IDW’10 Conference, Fukuoka, Japan, December, 2010. Fei Fan, Zourab Brodzeli, Vladimir Chigrinov, Anatoli Murauski, P - 2.220, 23d Intern. Liq. Cryst. Conf, Krakow, Poland, July 2010.